Personalisasi dan Big Data Analitik Sebagai Strategi Pemasaran di Era Society 5.0 - Nugrah Leksono Putri Handayani; Poppy Fitrijanti Soeparan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to find out how personalization and big data analytics can be used as an effective marketing strategies in the era of society 5.0. This research uses a qualitative method with a descriptive approach which aims to explore, analyze and interpret phenomena related to the topic. The data in this research was obtained through literature study, by exploring information from various primary and secondary sources consisting of books, scientific journals, articles and other relevant publications. The research results show that personalization and big data analytics are effective strategies in marketing in the era of society 5.0. personalization and utilizing big data analytics technology, companies can understand consumer behavior, optimize marketing campaigns, and manage customer relationships more effectively. So it can increase customer satisfaction and loyalty.